THE INFLUENCE OF CAREER DEVELOPMENT AND ORGANIZATIONAL CULTURE ON GEN Z EMPLOYEE RETENTION - Fitria, Novy; Muttaqien, Fauzan; Rizki, Via Lailatur (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2024)
This study aims to analyze the influence of career development and organizational culture on the retention of Generation Z employees. This study was conducted using a quantitative method using a sample of 76 Gen Z employees who have worked for at least 1 year. The results of the study indicate that career development and organizational culture significantly affect the retention of Gen Z employees, both partially and simultaneously. Structured career development and an inclusive organizational culture have been shown to increase employee retention. This study provides an important contribution to human resource management in facing the challenges of retaining young employees in the digital era.